Integrating Multicultural Values in Teaching Speaking - Lili Wahdini (Proceedings of ISELT FBS Universitas Negeri Padang, 2014)
To teach is to touch a life forever. Teachers and students are touching each other. Teachers facilitate and guide their students to achieve educational objectives. Teaching English means teaching the four integrated skills to the students, namely listening, speaking, reading and writing. Speaking is a difficult skill to teach, because learners have to master several different elements of language in order to say what they want to say, speaking is a process of transferring the information in a variety of contexts. In speaking activities students are expected to express their ideas and explore their though. There are four values of the multicultural education namely: (1) acceptance and appreciation of cultural diversity, (2) respect for human dignity and universal human rights, (3) responsibility to the world community, and (4) respect for the earth, in teaching process teacher should be able to integrate all the values in that process. Teacher should teach in a multicultural manner means that they have to creating classroom environment where students are respected, cared and encouraged to develop their potential. Speaking class is the appropriate class to promote the multicultural values; those values could be as a topic for the student’s discussion, or as a theme for their role play. There are several steps of integrating multicultural values in speaking, the steps are as follows: (1) discussion multicultural values (2) exploring and elaborating multicultural value in group discussion, role play and problem solving activities. As a conclusion, we can use learning speaking to develop multicultural values for the students. Teaching and learning is our tools to change and build student characters.